Noology and reology: how to use Zubiri’s Legacy today - Sierra-Lechuga, Carlos (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
I will formally present reology as a precise philosophy. Today we have to deal with our tools that can not be, for reasons we will see, neither classical epistemology nor ontology; we require «noology» and «reology», philosophies inchoated in the thought of Xavier Zubiri. Taking the noology by realism of departure in which «reality is» the way of remaining things in the apprehension, and the reology by realism of arrival in which the structural constitution of things «is reality», metaphysics is purged of ancient ballasts. Everything is presented in two parts: I) Shortage of reologists, we will explain what is meant by «noology» and by «reology». II) Reality, we will expose the problem of the «two» realisms («of departure» and «of arrival»), we will concretize it in the philosophy of Zubiri and we will see that «both» are rather one. We will conclude that, if we want to have a relevant philosophy for the contemporary knowledge of the world without restricting ourselves to a scholarly study of an author, we have to do reology.